2021
DOI: 10.1155/2021/6633297
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Novel Isoxazole-Amide Analogues as Anticancer and Antioxidant Agents

Abstract: Cancer now is one of the leading causes of mortality in the world. There has been a lot of effort to discover new anticarcinogenic agents that allow treatment with fewer side effects. A series of isoxazole-carboxamide derivatives (2a–2g) were synthesised and evaluated for their cytotoxic activity against breast (MCF-7), cervical (HeLa), and liver (Hep3B) cancer cell lines and their antioxidant activity in the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. The results showed that 2d and 2e were the most active com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…To ensure that only DNA was stained, the treatment of cells with ribonuclease (50 μl of 100 μg/ml RNase) was done. en, cells were stained with 5 μl of 50 μg propidium iodide/100 ml and were analyzed using the flow cytometer (Becton-Dickinson LSR II, Immunofluorometry systems, Mountain View, CA) [29].…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…To ensure that only DNA was stained, the treatment of cells with ribonuclease (50 μl of 100 μg/ml RNase) was done. en, cells were stained with 5 μl of 50 μg propidium iodide/100 ml and were analyzed using the flow cytometer (Becton-Dickinson LSR II, Immunofluorometry systems, Mountain View, CA) [29].…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…The isoxazole carboxamide derivatives were also assessed for their cytotoxic activity on breast (MCF-7) and liver (Hep3B) cancer cell lines, as well as on the cervix (HeLa). Only two compounds from this series showed promising anticancer activity, delaying the G2/M phase by 18.07% [22].…”
Section: Discussionmentioning
confidence: 96%
“…Chemotherapy is widely used, especially against inoperable tumors, as a basic therapy or as an adjunct treatment before and/or after subsequent treatment. However, the use of chemotherapy is limited because it has a poor efficacy; minimal target cell selectivity; and undesirable side effects, such as alopecia, nausea, and vomiting [22]. It is very important to search for new components of oncological therapy that will ensure the greater effectiveness of the therapy and, at the same time, will be free from troublesome side effects reducing the quality of life of an oncological patient.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, nicotinamidemoiety was utilized as a head in the synthesized compounds to maintain the essential H-bonding interaction at the hinge region. In addition, it was reported that amide moiety may exert an anticancer effect [33]. With respect to the linker segment, it is usually 3-5 bond lengths [34].…”
Section: Rationale and Designmentioning
confidence: 99%